Proses Peradilan terhadap Pelaku Pengulangan Tindak Pidana Pencurian Ringan di Pengadilan Negeri Pulau Punjung: Studi Kasus Putusan Nomor: 8/Pid.C/2020/PN Plj - Priyanti, Dita Anisya; Ikhwan, Muhammad; Badri, Ainul (VISA: Journal of Vision and Ideas, 2024)
The judicial process for perpetrators of repeat crimes of light theft should be processed using a regular examination or short examination, while at the Pulau Punjung District Court, cases of repeat crimes of light theft are processed using a speedy examination. The aim of writing this thesis is to understand the judicial process regarding the examination of perpetrators of repeat crimes of petty theft at the Pulau Punjung District Court, as well as to determine the Judge's obstacles in deciding the speedy trial process in case Number: 8/Pid.C/2020/PN Plj at the District Court Pulau Punjung. This legal research is empirical juridical research, namely research that uses field object data or is based on actual conditions. The results of writing this thesis show that: the judicial process for examining perpetrators of repeat crimes of petty theft at the Pulau Punjung District Court has not been effective, especially in case Number: 8/Pid.C/2020/PN Plj which is still being processed using a quick examination process, where the process Rapid examinations can only be carried out in cases of minor criminal offenses which are not repetitions of criminal acts (recidivism), the examination process for repetitions of minor criminal acts should be carried out using ordinary and short examination procedures. The judge's obstacles in deciding the speedy examination process in this case were the lack of accuracy in handing over the case files at the time of registration where one of the defendants was a repeat criminal, as well as the lack of communication and coordination between law enforcement agencies, namely investigators and prosecutors.